Factors Associated with Glycemic Control Among People with Type 2 Diabetes Mellitus in Sub-district, Ubon Ratchathani - ทองโปร่ง, ปิยะวดี (Journal of Ratchathani Innovative Health Sciences, 2019)
The Objective of this survey research was to study the relationship between personal factors, knowledge of diabetes, social support, health care behaviors and glycemic control in type 2 diabetes mellitus patients. The sample was 118 type 2 diabetes mellitus patients receiving services in diabetic clinic, Nong Kin Phen Tambon Health Promoting Hospital, Warinchamrab Ubon Ratchathani, during April-May 2018. Data collection instruments used in the study were questionnaires consisting of personal information, knowledge of diabetes, social support and health care behaviors. The reliability of the knowledge questionnaires was KR-20 = 0.67, social support and health care behaviors questionnaires was Cronbach’s Alpha Coefficient of 0.78 and 0.85, respectively. The data were analyzed by using frequency, percentage, mean, standard deviation and Chi–square test (x2). The result showed that the knowledge of diabetes, social support and health care behaviors were at high levels (60.17, 52.54 and 71.19 Percent, respectively). For the relationship study, the body mass index and the follow up by appointment were associated with glycemic control, statistically significant at the 0.05 level. However, there was no significant association between knowledge of diabetes, social support, health behavior and glycemic control. The results showed that the development of models of care for type 2 DM patients must take body mass index and the follow up by appointment, by focusing on the individual needs of the patients to response appropriately, leading to better self-care and blood sugar control among the patients.